Characterization of new microsatellite markers from sugarcane (Saccharum officinarum) transcriptome - Gao, Yijing; Zhou, Hui; Liu, Junxian; Lei, Jingchao; Duan, Weixing; Yang, Cuifang; Zhou, Shan; Li, Xiang; Zhang, Gemin; Zhang, Baoqing; Tan, Hongwei; Wang, Zeping; et al. (The Indian Journal of Agricultural Sciences, 2020)
Microsatellites, or simple sequence repeats (SSR), developed by expressed sequence tag (EST) databases is an economical and efficient tools that can be used to perform genetic investigations at a functional level. Here, a new sugarcane database of transcriptome from our variety, GT35, was examined for the presence of SSRs. To test the utility of EST-derived SSR markers, a total of 51 new EST-SSRs were identified for possible use as potential genetic markers from no redundant SSR-positive ESTs, which were unmapped with the sequences available in the NCBI’EST database of sugarcane by BLASTN. Polymorphisms of the identified 51 EST-SSR markers were evaluated in 21 sugarcane genotypes, planted and collected in 2013 at Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences (SRI-GXAAS) in China. High polymorphisms were detected in terms of number of alleles ranging from 5-36 with an average of 16.8 per locus and polymorphism information content values ranging from 0.74 to 0.95 with a mean of 0.92. Average transferability to Erianthus arundinaceus and Narenga porphyrocoma was 23.9% and 34.4%, respectively. The ability to establish genetic relationship was analyzed by cluster analysis, the result of which revealed that the major grouping was in accordance with taxonomical classification. The development of new EST-SSR markers presented in this work will have important implications for genetic analysis and breeding.